Beneficiation of colemanite tailings by attrition and flotation - Gül, A.; Kaytaz, Y.; Önal, G. (Elsevier BV, 2006)
Abstract Boron minerals are generally concentrated using attrition methods followed by screening and classification to remove clay minerals in industrial scale. Physical concentration methods are used in Kestelek Boron Mine for the concentration of colemanite. Because of the inefficient process operation, the tailings containing about 20% B 2 O 3 are discarded into the tailings pond. In this study, colemanite tailings sample taken from tailings pond was treated using scrubbing + screening followed by flotation to recover the lost boron. As a result of the experimental studies, a concentrate containing 44.5% B 2 O 3 was produced with 68.4% B 2 O 3 recovery.